Memahami Komunikasi Beda Budaya Studi Kasus Pada Proses Adaptasi Kaum Expatriate Eropa dan Australia Terhadap Masyarakat Lokal Kota Semarang - Hardani, Martina Dwi (Jurnal The Messenger, 2012)
The research aims to understand how to communicate between culture of expatriate cross cultural adaptation process to local society in Semarang. Those, can seen from communing meaning process by language, culture, and lifestyle.The main theories used in this research is Interactional Symbolic Theory. There are three base of principal in Interactional Symbolic Theory by Blummer involve meaning, language, and thought. This permis leads to conclusion about persons self and their socialization to bigger community.Research Methodology used was qualitative descriptive is there search method that seeks to describe and interpret the object as it is, by describing systematically the facts and characteristics of the object studied properly. Data sampling using a purposive sampling that is based on the theoretical basis used, but it can grow as needed and steadiness in obtaining data. Sources studied are the expatriates who live in the city of Semarang. Informants were interviewed were three people who joined in Semarang Expatriate Community who have more than3 years and experiencing the cross culture.This research concluded that cross culture communication in adaptation process of the expatriate to Semarang community vulnerable on problems because of cultural differences, patterns of thought, behavior, and lifestyle habits so that anxiety and uncertainty lead to misunderstandings, and differences in communicating meaning. Therefore, in the process adaptation needs a high sense of empathy and good management meaning and mutual respecting   between different cultures to create a good living in different cultural society.